Advancing the understanding and management of angioimmunoblastic T-cell lymphoma: insights into its pathogenesis, clinical features, and emerging therapeutic strategies - Xing, Yurou; Huang, Junmeng; Zhang, Yi; Wang, Yongsheng; Qi, Shaochong (Frontiers in Oncology, 2025)
Angioimmunoblastic T-cell lymphoma (AITL) is a clinically aggressive non-Hodgkin lymphoma associated with many immune disorders. The incidence of AITL has gradually increased in Asia in recent years. Malignant AITL cells originate from T follicular helper cells, which have a unique morphology and complex biological characteristics. High-throughput sequencing studies have identified many gene mutations associated with its pathogenesis, including mutations in tet methylcytosine dioxygenase 2 (TET2), isocitrate dehydrogenase (NADP+) 2 (IDH2), DNA methyltransferase 3 alpha (DNMT3A), ras homolog family member A (RHOA), and T cell receptor-related genes. Currently, there is no standardized treatment for AITL, the first-line chemotherapy is ineffective, the recurrence rate is high, the overall prognosis of patients is poor, and the median survival time does not exceed three years. New drugs are urgently needed. However, with continuous in-depth study of the molecular genetic mechanism of AITL, some new drugs and therapies have been tested for patients with relapsed and refractory AITL, achieving some therapeutic effects. Increasing clinical studies are evaluating new potential targets for AITL based on specific molecular markers, gradually improving individualized treatment and ultimately improving the clinical prognosis of patients with AITL. This review first summarizes the progress of research on the etiology, clinical pathological characteristics, and molecular genetic mechanisms of AITL to enhance understanding of the disease. It then summarizes the progress of research on its treatment strategies to provide some references for clinically diagnosing and treating AITL.